Unilateral Hypoglossal Nerve Palsy after Use of the Laryngeal Mask Airway Supreme - Kenichi Takahoko; Hajime Iwasaki; Tomoki Sasakawa; Akihiro Suzuki; Hideki Matsumoto; Hiroshi Iwasaki (Case Reports in Anesthesiology)
Purpose. Hypoglossal nerve palsy after use of the laryngeal mask airway (LMA) is an exceptionally rare complication. We present the first case of unilateral hypoglossal nerve palsy after use of the LMA Supreme. Clinical Features. A healthy 67-year-old female was scheduled for a hallux valgus correction under general anesthesia combined with femoral and sciatic nerve blocks. A size 4 LMA Supreme was inserted successfully at the first attempt and the cuff was inflated with air at an intracuff pressure of 60 cmH2O using cuff pressure gauge. Anesthesia was maintained with oxygen, nitrous oxide (67%), and sevoflurane under spontaneous breathing. The surgery was uneventful and the duration of anesthesia was two hours. The LMA was removed as the patient woke and there were no immediate postoperative complications. The next morning, the patient complained of dysarthria and dysphasia. These symptoms were considered to be caused by the LMA compressing the nerve against the hyoid bone. Conservative treatment was chosen and the paralysis recovered completely after 5 months. Conclusion. Hypoglossal nerve injury may occur despite correct positioning of the LMA under the appropriate intracuff pressure. A follow-up period of at least 6 months should be taken into account for the recovery.